Standardisation of management after Norwood operation has not improved 1-year outcomes. (26th January 2021) - Pisesky, Andrea; Shah, Shilpa; Seed, Michael; Schwartz, Steven M.; Russell, Jennifer; Pereira-Solomos, Paula; Thomas, Jennifer; Van Arsdell, Glen; Floh, Alejandro
Abstract: Introduction: Treatment of hypoplastic left heart syndrome varies across institutions. This study examined the impact of introducing a standardised programme. Methods: This retrospective cohort study evaluated the effects of a comprehensive strategy on 1-year transplant-free survival with preserved ventricular and atrioventricular valve (AVV) function following a Norwood operation. This strategy included standardised operative and perioperative management and dedicated interstage monitoring. The post-implementation cohort (C2) was compared to historic controls (C1). Outcomes were assessed using logistic regression and Kaplan–Meier analysis. Results: The study included 105 patients, 76 in C1 and 29 in C2. Groups had similar baseline characteristics, including percentage with preserved ventricular (96% C1 versus 100% C2, p = 0.28) and AVV function (97% C1 versus 93% C2, p = 0.31). Perioperatively, C2 had higher indexed oxygen delivery (348 ± 67 ml/minute/m 2 C1 versus 402 ± 102ml/minute/m 2 C2, p = 0.015) and lower renal injury (47% C1 versus 3% C2, p = 0.004). The primary outcome was similar in both groups (49% C1 and 52% C2, p = 0.78), with comparable rates of death and transplantation (36% C1 versus 38% C2, p = 0.89) and ventricular (2% C1 versus 0% C2, p = 0.53) and AVV dysfunction (11% C1 versus 11% C2, p = 0.96) at 1-year. When accounting for cohort and 100-day freedom from hospitalisation, female gender (OR 3.7, p = 0.01) increased and ventricular dysfunction (OR 0.21, p = 0.02) and CPR (OR 0.11, p = 0.002) or ECMO use (OR 0.15, p = 001) decreased the likelihood of 1-year transplant-free survival. Conclusions: Standardised perioperative management was not associated with improved 1-year transplant-free survival. Post-operative ventricular or AVV dysfunction was the strongest predictor of 1-year mortality.